A Model for Aging in Place in Apartment Communities. Issue 1 (2nd January 2017) - Ewen, Heidi H.; Lewis, Denise C.; Carswell, Andrew T.; Emerson, Kerstin Gerst; Washington, Tiffany R.; Smith, Matthew Lee
ABSTRACT: The purpose of this article is to introduce a theoretical model for an aging-in-place housing specialist for those living in congregate housing facilities. A "needs assessment" tool is outlined to help facilitate the successful implementation of a Health and Aging Residential Service Coordinator (HARSC), both from a research perspective and from implementation of training curriculum for this specialized population. A model that provides both on- and off-site services is hypothesized to be most effective.